Downregulation of Thromboxane A2 Receptor Occurs Mainly via Nuclear Factor-KappaB Signaling Pathway in Rat Renal Artery. (9th July 2017) - Zhang, Yaping; Mi, Man; Xie, Yan-Hua; Wang, Si-Wang; Edvinsson, Lars; Xu, Cang-Bao
Abstract : Thromboxane A2 (TXA2 ) acts on TXA2 receptors (TP) to regulate renal artery blood flow and subsequently contributes to the pathogenesis of renal ischemia. The present study was designed to examine if nuclear factor-kappaB (NF- κ B) signaling pathway is involved in the downregulation of TP receptors in rat renal artery. Rat renal artery segments were organ cultured for 6 or 24 h. Downregulation of TP receptors was monitored using myograph (contractile function), real-time PCR (receptor mRNA), and immunohistochemistry (receptor protein). Specific inhibitors (MG-132 and BMS345541) for NF- κ B signaling pathway were used to dissect the underlying molecular mechanisms involved. Compared to fresh (noncultured) segments, organ culture of the renal artery segments for 24 h induced a significant rightward shift of U46619 (TP receptor agonist) contractile response curves (pEC50 : 6.89 ± 0.06 versus 6.48 ± 0.04, P < 0.001 ). This decreased contractile response to U46619 was paralleled with decreased TP receptor mRNA and protein expressions in the renal artery smooth muscle cells. Specific inhibitors (MG-132 and BMS345541) for NF- κ B signaling pathway significantly abolished the decreased TP protein expression and receptor-mediated contractions. In conclusion, downregulation of TP receptors in the renal artery smooth muscle cells occurs mainly via the NF- κ B signaling pathway.